Cover Feature: Tunable Light‐Emission Properties of Solution‐Processable N‐Heterocyclic Carbene Cyclometalated Gold(III) Complexes for Organic Light‐Emitting Diodes (Chem. Eur. J. 25/2021). Issue 25 (24th March 2021) - Malmberg, Robert; von Arx, Tobias; Hasan, Monirul; Blacque, Olivier; Shukla, Atul; McGregor, Sarah K. M.; Lo, Shih‐Chun; Namdas, Ebinazar B.; Venkatesan, Koushik
Abstract : N‐heterocyclic carbene (NHC) monocyclometalated gold(III) complexes : Highly efficient photoluminescence was achieved in the sky‐blue to green part of the electromagnetic spectrum using strong s‐donating cyclometalated NHC ligands and a dianionic (N N)‐type bidentate as the ancillary ligand. Detailed photophysical investigations supported by density functional theory calculations provide insights into the excited‐state properties of this new class of emitter molecules. The realization of the first solution‐processable OLED device based on these strongly luminescent gold(III) carbene emitter systems opens up exciting new opportunities in light emitting applications. More information can be found in the Full Paper by K. Venkatesan et al. on page 7265 .